Research Notes on Digital Business Transformation and Artificial Intelligence - Robert Leskovar; Borut Werber (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2025)
The book begins with cellular automata and their role in improving the strategic alignment of business and IT. It also presents research and practical insights for database designers and developers looking to utilise AI, insights into the societal dynamics shaping the adoption of microchip implants and their impact on digital transformation, the data maturity assessment model for SMEs, the legal framework and empirical findings on the adoption of e-invoicing, surveys and data analysis on key online shopping trends and preferences, a comprehensive overview of the revision of selected information security standards and their role in facilitating digital transformation, cyber security standards, insights into the role of AI in predictive analytics and preparing for future epidemic models, and finally new approaches and methodologies related to the functionality and security of facial recognition systems.